Distributive Justice in Plato and Aristotle - Knoll, Manuel (ΠΗΓΗ/FONS, 2019)
According to the prevailing opinion in German-speaking research, Aristotle is to be understood as the “discoverer” of particular justice. This article demonstrates that this view is incorrect, especially as Plato developed the doctrine of distributive justice and its principle of geometrical or proportional equality already previously in the Republic and the Laws. In a first step, this article interprets the doctrine of distributive justice that Aristotle lays out in the Nicomachean Ethics and the Politics. In a second step, it shows that the main elements of this doctrine have already been developed by Plato in the Laws. In a final step the article offers an innovative interpretation of the concept of justice that Plato presents in the Republic.
Keywords: Plato; Aristotle; Distributive justice; Republic; Laws